Design of a Transmission-line Transformer in the Construction of Strong Electromagnetic Field. Issue 5 (June 2019) - Lei, Zhang; Lewu, Deng; Ping, Wei; Peng, Cui
Abstract: Principle and design process of a transmission-line transformer are introduced in this paper. This design is mainly used to solve the problem of antenna impedance matching in the process of constructing strong electromagnetic environment, in order to improve the space radiation efficiency of low frequency band and realize the effective construction of strong electromagnetic environment.